Sexual violence against female children and adolescents - Guevara-Ríos, Enrique (2025)
Sexual violence against girls and adolescents constitutes a serious public health problem that violates fundamental rights and exposes victims to long-term physical, psychological, and social consequences. The magnitude and persistence of this phenomenon demands a coordinated response from all sectors of the government, especially the health sector.